Preferred and Actual Involvement of Advanced Lung Cancer Patients and Their Families in End-of-Life Decision Making: A Multicenter Study in 13 Hospitals in Flanders, Belgium - Pardon, Koen; Deschepper, Reginald; Vander Stichele, Robert; Bernheim, Jan L.; Mortier, Freddy; Schallier, Denis; Germonpré, Paul; Galdermans, Daniella; Kerckhoven, Willem Van; Deliens, Luc (Journal of pain and symptom management, 2012)
Death is often preceded by medical decisions that potentially shorten life (end-of-life decisions [ELDs]), for example, the decision to withhold or withdraw treatment. Respect for patient autonomy requires physicians to involve their patients in this decision making. The objective of this study was to examine the involvement of advanced lung cancer patients and their families in ELD making and compare their actual involvement with their previously stated preferences for involvement. Patients with Stage IIIb/IV non-small cell lung cancer were recruited by physicians in 13 hospitals and regularly interviewed between diagnosis and death. When the patient died, the specialist and general practitioner were asked to fill in a questionnaire. Eighty-five patients who died within 18 months of diagnosis were studied. An ELD was made in 52 cases (61%). According to the treating physician, half of the competent patients were not involved in the ELD making, one-quarter shared the decision with the physician, and one-quarter made the decision themselves. In the incompetent patients, family was involved in half of cases. Half of the competent patients were involved less than they had previously preferred, and 7% were more involved. Almost all of the incompetent patients had previously stated that they wanted their family involved in case of incompetence, but half did not achieve this. In half of the cases, advanced lung cancer patients—or their families in cases of incompetence—were not involved in ELD making, despite the wishes of most of them. Physicians should openly discuss ELDs and involvement preferences with their advanced lung cancer patients.